Acetic acid strengthens cell wall calcium pectate cross-linking in fresh carrot slices: Insights from pectin immunolabeling and calcium localization - Siyang Li; Fuzhen Yang; Xianqiang Chen; Ruibing Duan; Jie Li; Shoulei Yan (Food Hydrocolloids, 2026)

Effects of different storage conditions on postharvest characteristics and microbial community of lotus sprouts - Chunfang Xu; Xianqiang Chen; Ruibing Duan; Yanzhao Liu; Shoulei Yan; Jie Li (Food Chemistry, 2026)

NSUN2 Knockdown Promotes the Ferroptosis of Colorectal Cancer Cells Via m5C Modification of SLC7A11 mRNA - Ruibing Tong; Yuefeng Li; Junli Wang; Chengyu Liu; Yan Liu; Rongshuang Li; Xinghong Wang (Biochemical Genetics, 2026)

Recent advances in green modification of lotus rhizome starch: Physicochemical properties, techno-functional characteristics and challenges - Xianqiang Chen; Yanzhao Liu; Ruibing Duan; Yassin Haran; Siyang Li; Zhongyi Liu; Xiaoling Zeng; Zongyu Liu; Jie Li; Shoulei Yan (Food Chemistry, 2025)

Sensory and flavor profiling of lotus rhizome pork rib soup: Identification of optimal cultivars using HS-SPME-GC/MS, E-nose, and E-tongue analyses - Ruibing Duan; Xinyu Chen; Xianqiang Chen; Jie Li; Shoulei Yan (Food Chemistry, 2025)

Supramolecular host-guest interactions guided rapid biomineralization for blockade therapy of osteosarcoma - Beibei Xie; Yuanfu Ding; Ziyi Wang; Shengke Li; Yan Wang; Ruibing Wang; Shaowei Wang; Peng Li (Chemical Engineering Journal, 2025)

Coastal conversion alters topsoil carbon, nitrogen and phosphorus stocks and stoichiometric balances in subtropical coastal wetlands - Minjie Hu; Jingtao Wang; Jordi Sardans; Hui Wu; Ranxu Ni; Pingping Guo; Ruibing Yan; Haoyu Liao; Chunya Liu; Josep Peñuelas; Chuan Tong (Science of The Total Environment, 2024)

Formation mechanism of blue pigment in boiled lotus rhizome discs: Insight into the chelation of polyphenols and iron - Xianqiang Chen; Zhong Chen; Ruibing Duan; Shoulei Yan; Jie Li (Food Research International, 2024)

Bacterial and fungal communities exhibit contrasting patterns in response to marsh erosion: A fine-scale observation - Minjie Hu; Dongyao Sun; Jordi Sardans; Ruibing Yan; Hui Wu; Ranxu Ni; Josep Peñuelas (CATENA, 2024)

Microbial diversity and keystone species drive soil nutrient cycling and multifunctionality following mangrove restoration - Minjie Hu; Jordi Sardans; Dongyao Sun; Ruibing Yan; Hui Wu; Ranxu Ni; Josep Peñuelas (Environmental Research, 2024)

Coastal degradation regulates the availability and diffusion kinetics of phosphorus at the sediment-water interface: Mechanisms and environmental implications - Minjie Hu; Ruibing Yan; Ranxu Ni; Hui Wu (Water Research, 2024)

Linking soil phosphorus availability and phosphatase functional genes to coastal marsh erosion: Implications for nutrient cycling and wetland restoration - Minjie Hu; Ruibing Yan; Hui Wu; Ranxu Ni; Dianquan Zhang; Shuangquan Zou (Science of The Total Environment, 2023)

Establishment and clinical application evaluations of a deep mining strategy of plasma proteomics based on nanomaterial protein coronas - Jianan Wang; Wei Xie; Longqin Sun; Jingli Li; Songfeng Wu; Ruibing Li; Yan Zhao (Analytica Chimica Acta, 2023)

Substantial increase in P release following conversion of coastal wetlands to aquaculture ponds from altered kinetic exchange and resupply capacity - Minjie Hu; Jordi Sardans; Ruibing Yan; Hui Wu; Ranxu Ni; Josep Peñuelas; Chuan Tong (Water Research, 2023)

Coastal wetland conversion to aquaculture pond reduced soil P availability by altering P fractions, phosphatase activity, and associated microbial properties - Minjie Hu; Jordi Sardans; Yixun Le; Ruibing Yan; Josep Peñuelas (Chemosphere, 2023)

Moderate salinity improves the availability of soil P by regulating P‐cycling microbial communities in coastal wetlands - Minjie Hu; Yixun Le; Jordi Sardans; Ruibing Yan; Yi Zhong; Dongyao Sun; Chuan Tong; Josep Peñuelas (Global Change Biology, 2023)
Accelerated sea‐level rise is expected to cause the salinization of freshwater wetlands, but the responses to salinity of the availability of soil phosphorus (P) and of microbial genes involved in the cycling of P remain unexplored. We conducted a field experiment to investigate the effects of salinity on P cycling by soil microbial communities and their regulatory roles on P availability in coastal freshwater and brackish wetlands. Salinity was positively correlated with P availability, with higher concentrations of labile P but lower concentrations of moderately labile P in the brackish wetland. The diversity and richness of microbial communities involved in P cycling were higher in the brackish wetland than the freshwater wetland. Salinity substantially altered the composition of the P‐cycling microbial community, in which those of the brackish wetland were separated from those of the freshwater wetland. Metagenomic sequence analysis indicated that functional genes involved in the solubilization of inorganic P and the subsequent transport and regulation of P were more abundant in coastal soils. The relative abundances of most of the target genes differed between the wetlands, with higher abundances of P‐solubilization ( gcd and ppa ) and ‐mineralization ( phoD , phy , and ugpQ ) genes and lower abundances of P‐transport genes ( pstB , ugpA , ugpB , ugpE , and pit ) in the brackish wetland. A significant positive correlation between the concentration of labile P and the abundances of the target genes suggested that salinity may, at least in part, improve P availability by regulating the P‐cycling microbial community. Our results suggest that the P‐cycling microbial community abundance and P availability respond positively to moderate increases in salinity by promoting the microbial solubilization and mineralization of soil P. Changes in microbial communities and microbially mediated P cycling may represent microbial strategies to adapt to moderate salinity levels, which in turn control soil function and nutrient balance.

Marker-free lines of phytase-transgenic Brassica napus show enhanced ability to utilize phytate - Li Xu; Lingyi Zeng; Li Ren; Wang Chen; Fan Liu; Huan Yang; Ruibing Yan; Kunrong Chen; Xiaoping Fang (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Biomedical applications of Aloe vera - Yan Gao; Kit Ieng Kuok; Ying Jin; Ruibing Wang (Critical Reviews in Food Science and Nutrition, 2019)